Lengua y mercado en el mundo hispanohablante: un acercamiento al estado de la traducción literaria - Calabrese Steimberg, Laura (Linguistica Antverpiensia, New Series – Themes in Translation Studies, 2021)
This paper analyzes the status of literary translation in Spanish America and its conditions of production. Working with the Argentinean case as an exam-ple, we try to explain the logic of a cultural field strongly shaped by editorial globalization and economic dependency on the former home country. We discuss a number of theoretical issues related to the possible existence of a mega-polysystem linking the Spanish-speaking countries and their literary systems, as a way to approach the complex relations between a supraregional language and the national States sharing it. In this context, we analyze the unequal distribution of Spanish dialectal variations in the verbal market, and we examine the strategies that aim at resisting this kind of cultural dependency.